Long-term follow-up of composite bladder augmentation incorporating stomach in a multi-institutional cohort of patients with cloacal exstrophy. Issue 1 (February 2017) - Casey, J.T.; Chan, K.H.; Hasegawa, Y.; Large, T.; Judge, B.; Kaefer, M.; Misseri, R.; Rink, R.C.; Ueoka, K.; Cain, M.P.
Summary: Introduction: Composite bladder augmentation, incorporating gastric and bowel segments, has the theoretical advantage of metabolic neutrality while potentially avoiding the morbidities of gastrocystoplasty, such as hematuria-dysuria syndrome. The most common indication for this operation is a paucity of bowel, such as in cloacal exstrophy. Despite several early descriptive studies of this technique, there are no reports, to date, of long-term follow-up in this population. Objective: To describe the outcomes of composite bladder augmentation utilizing stomach in a cohort of cloacal exstrophy patients. Materials and Methods: A retrospective review of cloacal exstrophy patients who underwent composite bladder augmentation from 1984 to 2006 at two institutions was performed. The incidence of mortality and morbidities related to augmentation was evaluated. Results: Eleven patients with cloacal exstrophy underwent composite bladder augmentation. Median age at initial augmentation was 6.4 years (interquartile range (IQR) 4.4–9.1). Median follow-up was 13.2 years (IQR 11.2–24.6). The Summary table describes the types of composite bladder augmentations. Of the three patients with pre-operative metabolic acidosis, two improved with composite bladder augmentation and one developed metabolic alkalosis. Three developed hematuria-dysuria syndrome: one improved with staged ileocystoplasty, and two had persistent symptoms successfully treated with H2 receptor blockers. Two of 11 developed symptomatic bladder stones. There were no reported bladder perforations, bladder malignancies, conversions to incontinent urinary diversions, or deaths. Conclusion: With long-term follow-up, very few patients developed metabolic acidosis/alkalosis after composite bladder augmentation. The composite bladder augmentation will continue to be used in patients with cloacal exstrophy, in order to minimize the impact on the pre-existing short gut in these patients. Summary table Description of the types of composite bladder augmentations. Type of composite bladder augmentation Number of patients (%) Gastrocystoplasty onto hindgut incorporated during initial bladder closure 2 (18.2%) Gastrocystoplasty with subsequent ileocystoplasty 2 (18.2%) Initial composite bladder augmentation with both stomach and ileum 5 (45.5%) Multiple augmentations with a final composition of stomach and ileum 2 (18.2%)